IMPROVEMENT OF INVESTMENT PROJECT MANAGEMENT METHODOLOGY IN TEXTILE INDUSTRY BASED ON CLUSTER APPROACH (Marketing Journal, 2026)
This article analyzes the theoretical and practical aspects of the cluster approach in the context of improving the methodology of investment project management in the textile industry. Using the case of Uzbekistanʼs textile clusters, mechanisms for enhanc ing project efficiency have been examined. A comparative analysis of international cluster development practices has been conducted, and recommendations have been formulated for national industry advancement.
Keywords: textile industry; investment projects; cluster approach; project management; value chain; competitiveness